Upaya Meningkatan Motivasi Belajar Tingkat Sekolah Dasar Melalui Kegiatan Bimbingan Belajar Gratis Di Kelurahan Tamansari, Kecamatan Pulomerak, Kota Cilegon - Asih Setyo Rini; Irfan Muhammad; Siti Hanan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The lack of knowledge of parents of students about the importance of education for the basis of a decent job and income in the future is the main thing in holding free tutoring at Tamansari Village, Pulomerak District, Cilegon City - Banten. This underlies the Lecturers and Students of the Community Work Lecture (KKM) at Bina Bangsa University, especially Group 72, to help efforts to increase learning motivation at the Elementary School (SD) level to participate in this activity enthusiastically. The method of implementing activities carried out using participatory, where participatory is a technique for managing the relationship of involvement of individuals in planning a number of activities for common goals and solutions. Several stages help increase learning motivation in the implementation of community service: (1) warming up before delivering material, namely providing learning motivation with inspirational stories, (2) presentation of material, (3) Questions and Answers, (4) Games and (5) giving gifts and praise . The results of the tutoring activities for each session are divided into 2 groups, adjusted to the grade level of each student (children). Group 1 consists of classes 1 to 3, while group 2 consists of classes 2 to 6. Prizes are given in the form of grades for group 1 with an average score of 85 and group 2 with an average score of 80. This shows that the material presented can be accepted by students